Association between the red cell distribution width-to-albumin ratio and recurrence-free survival and overall survival in patients with non-muscle-invasive bladder cancer: a retrospective cohort study - Song, Feifan; Su, Shiqiang; Zhang, Xueqiao; Cao, Yunpeng; Cui, Xiongjie; Zhang, Lili; Li, Chao; Li, Shen (Frontiers in Oncology, 2026)
BackgroundThe prognostic utility of the red cell distribution width-to-albumin ratio (RAR) in non-muscle-invasive bladder cancer (NMIBC) has not been established. This study aimed to evaluate the associations between preoperative RAR and both recurrence-free survival (RFS) and overall survival (OS) in patients with NMIBC.MethodsA retrospective review was performed for 240 individuals with NMIBC having undergone transurethral resection of bladder tumor (TURBT) at Shijiazhuang People’s Hospital from November 2013 to January 2024. Demographic characteristics, hematological parameters, pathological data, and information on instillation therapy were collected. The optimal RAR cutoff was identified by applying receiver operating characteristic (ROC) analysis. Survival curves were generated via the Kaplan–Meier method. The relationships of RAR with both RFS and OS were examined using univariate and multivariate Cox proportional hazards regression models. A nomogram was created using the identified independent prognostic factors from multivariate analysis to predict RFS. The discriminative ability and clinical usefulness of the nomogram were assessed by the concordance index (C-index), the calibration plots, time-dependent ROC analysis, and decision curve analysis (DCA).ResultsPatients with higher preoperative RAR showed significantly poorer RFS and OS. Multivariate analysis identified high RAR as an independent prognostic factor for both RFS (HR: 1.731, 95% CI: 1.012 - 2.959) and OS (HR: 3.425, 95% CI: 1.196 - 9.806) in NMIBC patients. Based on these findings, RAR was incorporated into a nomogram model for predicting RFS. Compared to the baseline model without RAR, the new model exhibited an improved C-index (from 0.704 to 0.728). The calibration plots demonstrated excellent consistency of the nomogram-predicted probabilities for 1-, 3-, and 5-year RFS with the actual survival rates. The time-dependent ROC analysis revealed that the areas under the curve (AUC) values for RFS predictions at 1-, 3-, and 5- years were 0.806, 0.797 and 0.806. DCA validated that the nomogram yielded a superior net benefit within threshold probability ranges of 10% to 45% when compared to traditional staging systems.ConclusionsThe findings suggest that preoperative RAR serves as a novel and independent prognostic factor for predicting RFS and OS in NMIBC cases.